Selenium species in vegetables: benefits and toxicity for the body - Alya Luthfiyani Heryadi; Ayu Shalihat; Rimadani Pratiwi; Mutakin Mutakin (Universitas Islam Indonesia, 2020)
Abstract Background: Selenium is one of the essential trace elements in various biological body functions. The main source of Selenium in the body is food, one of which is vegetables. Vegetables collect Selenium from the soil which is then converted into various chemical species of Selenium. Such species should be recognized since each has different biological activities.Objective: The aim of this review was to identify chemical species of Selenium in vegetables as well as the benefits and toxicity for the body.Methods: Reference searches were done in Pubmed and Google Scholar databases with the keywords Selenium speciation in plants, selenite, selenate, selenomethionine, selenocystine, and se-methylselenocysteineResults: The results of speciation in several types of vegetables showed that the chemical species of Selenium abundantly found in vegetables were selenomethionine (SeMet), selenocystine (SeCys2) and se-methylselenocysteine (Se-MeSeCys), gamma-glutamyl-Se-methyl-selenocysteine, and inorganic species. Both Selenium-enriched vegetables and the species contained therein have a variety of benefits for the body. However, excessive consumption can also cause toxic effects.Conclusion: The chemical species of Selenium in vegetables can be either organic or inorganic. Both types of species have different benefits and toxic effects. Keywords: benefits, chemical species, Selenium, toxicity, vegetable Intisari Latar belakang: Selenium merupakan salah satu trace element esensial yang penting pada berbagai fungsi biologi tubuh. Sumber utama Selenium dalam tubuh adalah makanan, salah satunya yaitu sayuran. Sayuran mendapatkan Selenium dari tanah yang kemudian diubah menjadi berbagai spesies kimia Selenium. Spesies kimia Selenium penting untuk diketahui karena setiap spesies memiliki aktivitas biologi yang berbeda Tujuan: Review ini ditujukan untuk mengetahui spesies kimia Selenium yang terdapat pada sayuran serta manfaat dan toksisitasnya bagi tubuh Metode: Penelusuran referensi dilakukan melalui database Pubmed dan Google Scholar, dengan kata kunci Selenium speciation in plant, selenite, selenate, selenomethionine, selenocystine, dan se-methylselenocysteineHasil: Hasil spesiasi pada beberapa sayuran menunjukkan spesies kimia Selenium yang banyak terdapat dalam sayuran adalah selenomethionine (SeMet), selenocystine (SeCys2), dan Se-methylselenocysteine (Se-MeSeCys), gamma-glutamyl-Se-methyl-selenocysteine, dan spesies anorganik. Baik sayuran yang diperkaya Selenium maupun spesies yang terkandung di dalamnya memiliki berbagai manfaat bagi tubuh. Namun konsumsi yang berlebih juga dapat menyebabkan efek toksik Kesimpulan: Spesies kimia Selenium yang terdapat pada sayuran dapat berupa spesies organik maupun spesies anorganik. Kedua jenis spesies ini memiliki manfaat serta efek toksik yang berbedaKata kunci : manfaat, sayuran, Selenium, spesies kimia, toksisitas